Protein regulatory network mediated by palmitoylation modifications in the pathological progression of Parkinson’s disease: a narrative review - Liu, Jingjing; Wang, Shanshan; Fan, Lei; Zhou, Xin; Zhang, Sen; Wang, Qinglu; Dong, Panpan; Yu, Bo (Frontiers in Immunology, 2025)
Palmitoylation is a reversible lipid modification regulated by palmitoyl transferases and acyl-protein thioesterases, in which palmitic acid is attached to protein cysteine residues. This modification plays a pivotal role in modulating membrane localization and protein stability, and its dysregulation is closely associated with various neurodegenerative diseases, including Parkinson’s disease (PD). In PD, synaptotagmin-11, encoded by the PD risk gene SYT11, has been shown to reduce physiological α-synuclein (α-syn) tetramer formation while promoting the aggregation-prone monomeric form in a palmitoylation-dependent manner. In the context of PD, inflammation generally precedes the abnormal aggregation of α-syn and the degeneration of dopaminergic neurons (DA). Microglial activation, regarded as an inflammatory state, is facilitated by the palmitoylation-dependent localization of NLRP3 to the trans-Golgi network, which promotes the activation and expression of the NLRP3 inflammasome, leading to DA neuron loss. Additionally, the DJ-1 protein, encoded by the risk gene PARK7, and the dopamine transporter both undergo palmitoylation and may contribute to disease progression. This review summarizes the emerging link between protein palmitoylation and PD pathogenesis. Understanding the dynamic regulatory mechanisms of palmitoylation and depalmitoylation may facilitate the development of targeted therapeutic strategies for PD.